(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The apprenticeship program is a form of cooperation from several parties, in this case the Indonesian State and the Japanese State to improve good relations in forming equality in developments in certain fields, and aims to carry out skills transfer and so on and foster human resources that contribute to industrial development, increase mutual understanding and friendship between the two countries, by teaching the skills, technology, or knowledge possessed by the Japanese State to apprentice participants by referring to the laws of the two countries. The author carries out street vendors at the JLMC (Japanese Language & Management Center) which are carried out from July 17, 2019 to August 19, 2019. JLMC is located on Jl. W. R. Supratman No. 3, Cihapit, Kec. Bandung Wetan, Bandung City, West Java 40114. The purpose of this Field Work Practice is to find out the appeal of the apprenticeship program implemented at the JLMC LPK PT. OS Selnajaya and to find out the background of the apprenticeship choose an apprenticeship program at the JLMC LPK PT. Selnajaya OS. The author uses a descriptive method which is a method for making reports through direct observation in the field and collecting data from the company. The author also conducts limited interviews with company employees. The conclusion of the writing of this Final Project is the appeal of the apprenticeship program in the JLMC LPK PT. OS Selnajaya is a clear / certain apprenticeship program because apprentices who carry out apprenticeships will definitely leave for Japan. That also motivated the apprentice to choose the apprenticeship program in the JLMC LPK PT. Selnajaya OS.